Immunopathological comparison of in ovo and post-hatch vaccination techniques for infectious bursal disease vaccine in layer chicks - Zaheer, Iqra; Chen, Wei; Khan, Ahrar; Elokil, Abdelmotaleb; Saleemi, Muhammad Kashif; Zaheer, Tean; Khan, Muhammad Zargham (Frontiers in Veterinary Science, 2022)
The present study was designed to compare immunopathological effects of in ovo vaccination with post hatch vaccination against IBD in White Leghorn chicks. A total of 189 embryonated eggs were divided into six groups. At day 18 of incubation, groups A-C were administered in ovo with 228E, Winterfield 2512:10/3 and 2512/90:10/2.7, respectively, group D (post hatch vaccination) group E as shamed control (for quality evaluation of in ovo vaccination technique) & group F was control. The results showed that antibody titers against IBD detected by ELISA on day 2, 17 and 28 were significantly higher in all in ovo groups as compared to control groups E and F. On day 17, all vaccinated groups (in ovo and post-hatch vaccinated) showed no significant differences in antibody titers among themselves, however, at day 28 only the post hatch group showed significantly higher antibody titers followed by in ovo vaccinated groups. The cell mediated immunity determined by PHA-P assay was significantly higher in all vaccinated groups than the non-vaccinated groups. No clinical signs of IBD infection were observed in any of the vaccinated groups. There was only increase in bursa size of groups vaccinated with intermediate plus strains (groups A, C and D) at day 28. The histopathology showed that all the treatment groups had mild lesions induced by IBD virus in bursa. This study concluded that in ovo vaccination with live IBD vaccines provides protective immunity to the chickens even in the presence of IBD specific MDA, therefore the onset of immunity was much earlier than the post hatch vaccination and in ovo groups also maintained protective immunity against IBD for longer time.